Analysis of Hadith Criticism About Talaq in Emotional Conditions (Examination of Hadith presented by Ust Farhan Mauludi in Tiktok) - Jahira Salsabila Nurul Imam (Penerbit Hellow Pustaka, 2025)
This study analyzes the criticism of hadith regarding divorce pronounced in emotional states, as presented in Ust. Farhan Mauludi's lecture on the TikTok platform. The research aims to evaluate the authenticity of the hadith based on sanad and matan criticism methods and examine its impact on public understanding. Using a descriptive qualitative approach, data were obtained through lecture transcripts, hadith review from primary sources, and interviews with hadith experts. The findings indicate that the hadith concerning divorce in emotional states has varying levels of authenticity in primary hadith collections. Contextual interpretation is crucial to addressing the challenges of da'wah in the digital era. This study contributes to understanding how social media serves as an effective medium for delivering religious messages while emphasizing the importance of caution in presenting hadith to the public.